Oral intramuscular hemangioma: Report of three cases - Lescura, Carlos M. [UNESP]; de Andrade, Bruno A. B.; Bezerra, Kelly T.; Agostini, Michelle; Ankha, Milagros V. A. [UNESP]; de Castro, Felix; Carvalho, Yasmin R. [UNESP]; Romañach, Mário J.; Anbinder, Ana Lia [UNESP] (Wiley, 2019)
Intramuscular hemangioma (IMH) represents less than 1% of all hemangiomas. In the head and neck region, it occurs mostly in the masseter, temporalis and sternocleidomastoid muscles. Despite its infiltrative growth pattern and several worrisome histological features, such as increased mitotic activity, plumpness of the nuclei, intraluminal papillary projections or perineural infiltration, the lesion is benign, and complete surgical excision is the preferred treatment for such oral lesions. Herein, we report three rare cases of IMH in the tongue and lip, discuss the clinical and histological aspects, and review the literature regarding this lesion.
Keywords: intramuscular hemangioma; vascular malformations; vascular tumors